2011 Grants Programs : Projects Funded. - Australian Learning and Teaching Council (Australian Learning and Teaching Council (ALTC), 2011)
The Grants Scheme enables the Australian Learning and Teaching Council Limited (ALTC) to realise its designated responsibility to provide grants for academics and professional staff to investigate, develop and implement innovations in learning and teaching, and to develop leadership capabilities This report contains summaries of the 104 projects funded across the four programs of the Grants Scheme in 2011.